1982
DOI: 10.1007/bf01675870
|View full text |Cite
|
Sign up to set email alerts
|

Colour vision as a diagnostic aid

Abstract: The minimum requirements for a reliable study of (acquired) defects of colour vision have been formulated by Verriest. Taking these minimum requirements as a guide, about 200 patients were selected. For the differential diagnosis of disorders of the retina and the optic nerve the determination of the neutral zone and examination with the anomaloscope are important. This is true for both red-green and blue-yellow defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

1984
1984
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 10 publications
1
4
0
1
Order By: Relevance
“…These results are in agreement with previous studies suggesting that the SPP Part 2 able to identify acquired BY and RG deficiency [4,[9][10][11]. On the other hand, other researchers have found that the color vision losses in RPs could be either BY or RG deficiencies [1,2,4]. One possible explanation is that the color vision tests used in those experiments were not specifically designed to detect acquired color vision loss.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…These results are in agreement with previous studies suggesting that the SPP Part 2 able to identify acquired BY and RG deficiency [4,[9][10][11]. On the other hand, other researchers have found that the color vision losses in RPs could be either BY or RG deficiencies [1,2,4]. One possible explanation is that the color vision tests used in those experiments were not specifically designed to detect acquired color vision loss.…”
Section: Discussionsupporting
confidence: 93%
“…Color vision is well known to be affected in retinitis pigmentosa (RP) [1][2][3][4]. However, identifying the type of acquired color vision loss in RP may not be straightforward.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As to the other colour vision tests used for this comparative study, all the subjects were examined under standardized conditions: 6 Philips fluorescent tubes colour 57, colour rendering index 96, providing 1750 lux at the level of the test table. A test battery was used including plate tests, the Farnsworth-Munsell 100 Hue test and derivative tests, and an anomaloscope (Pinckers 1980(Pinckers , 1982.…”
Section: Methodsmentioning
confidence: 99%